2019
DOI: 10.20546/ijcrar.2019.702.006
|View full text |Cite
|
Sign up to set email alerts
|

Areas of Utilization of Orıganum acutidens (HAND.-MAZZ.) Ietswaart and Carvacrol

Abstract: Article InfoOriganum acutidens (Hand.-Mazz.) Ietswaart is an endemic plant growing in the eastern part of Turkey. Origanum acutidens, rich in rosmarinic acid, has a high antioxidant effect. The essential oil of this plant is rich in carvacrol. The plant has chemotypes containing up to 90% carvacrol. Carvacrol also has a comprehensive range of uses from health to food. According to results obtained from previous studies, carvacrol has a lethal effect against some cancer cells. Furthermore, carvacrol has antifu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 40 publications
(54 reference statements)
0
4
0
Order By: Relevance
“…O. acutidens is used as herbal tea by the people in the region where it grows (Tumen et al, 1995). It is known that this plant has antimicrobial and insecticidal effects, antitumor effects and antioxidant effects due to its high content of carvacrol (Karagoz & Parlakova Karagoz, 2019). In addition, it has the potential to become an ornamental plant with its magnificent appearance (Karagoz et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…O. acutidens is used as herbal tea by the people in the region where it grows (Tumen et al, 1995). It is known that this plant has antimicrobial and insecticidal effects, antitumor effects and antioxidant effects due to its high content of carvacrol (Karagoz & Parlakova Karagoz, 2019). In addition, it has the potential to become an ornamental plant with its magnificent appearance (Karagoz et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Ietsw. is a herbaceous perennial plant, flowering between June and August in Eastern Anatolia (Davis, 1982;Ietswaart , 1980) Growing on limestone and in noncalcareous soils between 1000-3000 m, sometimes in shady places, the plant needs very little moisture during the growing season In addition, O. acutidens, which can be widely used in urban landscape management, has showy, bright pink flowers and is an ornamental plant preferred due to its aromatic scent and its capacity to attract butterflies and bees (Karagoz and Karagoz, 2019). The species, which can grow up to 50 cm in length, is in hairless form, and its leaves bear intense odor (Ietswaart, 1980).…”
Section: Introductionmentioning
confidence: 99%
“…O. acutidens, which is rich in carvacrol and thymol, is also rich in rosmarinic acid and therefore has antioxidant activity (Kordali et al, 2008). In addition, O. acutidens growing in the Eastern Anatolia region contains >20% thymol (Karagoz and Karagoz, 2019;Kordali et al, 2008). Essential oil yields of O. acutidens range from 0.73 to 1.7% Nat.…”
Section: Introductionmentioning
confidence: 99%
“…were the primary components of the essential oils of O. acutidens (Baser et al, [2]; Sokmen et al, [6]; Figueredo et al, [4]). Kordali et al [5] reported that O. acutidens essential oil and its aromatic monoterpene components showed potent antifungal activity against plant pathogens, fungi and phytotoxic effects against A. retroflexus, R. crispus and C. Albüm (Karagoz and Parlakova Karagoz, [7]).…”
Section: Introductionmentioning
confidence: 99%